Product Differentiation and Brand Image on Mobile Phone Purchasing Decision - Lulu Indriaty; Putri Firdiah Karim; Guntur Noerman Sanjaya (Wahana : Tridarma Perguruan Tinggi, 2025)
This study aims to determine the effect of product differentiation and brand image on mobile phone purchasing decisions (study at Toko Rejeki Seluler Merauke). The independent variables used in this study are product differentiation and brand image, while the dependent variable is the purchasing decision. The population used in this study was consumers who had purchased mobile phone products at Toko Rejeki Seluler Merauke, namely 50 respondents, with sampling using the same population formula as the sample, namely 50 respondents. The method used in this study was the random sampling method. The data collection technique used in this study was a quantitative questionnaire. The data analysis techniques used were descriptive statistical analysis and multiple regression analysis. The study results showed that partial product differentiation had a significant positive effect on purchasing decisions, and brand image had a positive and significant impact on buying decisions. The R Square (R²) value of 0.474 indicates that the magnitude of product differentiation and brand image on Purchase Interest is 47.4 percent. In comparison, the remaining 53.6 percent is explained by other variables outside the two variables above.